Ela faz a interlíngua dela: estudo exploratório sobre a aprendizagem dos possessivos de terceira pessoa do português brasileiro por falantes de espanhol - Granato, Matheus (2021)
This research aims to analyze the apprenticeship of possessive pronominal constructions of 3rd person from Brazilian Portuguese (BP) by Spanish speakers (SS), focusing on the pragmatic and discursive domain implied in its use. The investigation was motivated by the observation of occurrences of the simple possessive “seu” from the production of SS students, in contexts in which its use did not correspond to the preference of Brazilians, causing strangeness and possibly noise in communication when establishing references. This paper is an exploratory study, of a quali-quantitative nature and focused descriptive methodological basis, which had as theoretical framework the Interlanguage model for analysis (SELINKER, 1972). The investigation was based on a set of descriptive studies about the BP possessive pronominal system (NEVES, 1996; MÜLLER, 1997; MORAIS & RIBEIRO, 2014; GUEDES, 2017, among others) and from Spanish (FREITES BARROS, 2001; SÁNCHEZ AVENDAÑO, 2008, OROZCO, 2009, 2010; PEREIRA & MARCOTULIO, 2020), which indicate diverse factors as determiners on the variation of “seu”/”dele” and “su”/”de él”, involving the formality delineation of the text and the expression of referential contrast, besides the divergence in grammaticality of the dative constructions for the expression of inalienable possession. These differences merge in the perspective of González (1994) about the reverse asymmetries of BP and Spanish. For data elicitation, it was applied an online questionnaire to Brazilians (speakers of BP as a mother tongue) and to foreigners SS students of BP. The questionnaire consisted on a proposal of written production adapted from Gancedo Álvarez (2008), an acceptability test of “seu” and “dele” in contextualized sentences and the referential interpretation of “seu” in dialogues that reproduces the oral aspect. The results of the written production indicate the discontinuation of the dative structure for the inalienable possession expression and its substitution for genitive constructions. Concerning the acceptability tests and referential interpretation, the data supports, to some extent, some hypothesis of the research, suggesting divergence in the interpretation and evaluation of “seu” and “dele” by the participants from both groups.